The Impact of Academic Supervision and Principal Leadership Style on Teacher Professionalism: A Study of State Vocational Schools in Ogan Ilir District - Melati Utami; Rohana Rohana; Nur Ahyani (Journal of Social Work and Science Education, 2026)
This study aims to determine and analyze the influence of academic supervision and principal’s leadership style on teacher professionalism in state vocational high schools throughout Ogan Ilir Regency, Indonesia, both partially and simultaneously. Employing a quantitative approach with a correlational design, the sample consisted of 101 teachers selected from the target population. Data were collected through questionnaires and documentation, then analyzed using the SPSS program. The results conclude three main findings: first, academic supervision has a significant influence on teacher professionalism; second, principal’s leadership style also significantly influences teacher professionalism; and third, academic supervision and principal’s leadership style together exert a significant combined influence on teacher professionalism. The study concludes that enhancing teacher professionalism in vocational high schools requires strengthening both academic supervision practices and principal leadership styles concurrently. The novelty lies in examining the combined effects of these two variables specifically within the context of state vocational high schools in Ogan Ilir Regency, an under-researched setting in Indonesian vocational education literature. Practically, the findings suggest that school principals should balance structured academic supervision with adaptive leadership styles tailored to vocational education demands, while policymakers should integrate both elements into principal training programs and teacher professional development initiatives. This study contributes to educational management literature by providing empirical evidence that academic supervision and leadership style function as complementary rather than competing factors in fostering teacher professionalism, particularly within vocational secondary education contexts.